Perkawinan Lesbian, Gay, Biseksual, dan Transgender dalam Perspektif Hukum Islam dan Hukum Positif - Mulyono Mulyono (Institut Agama Islam Negeri Curup, 2019)
This article aims to conduct an in-depth comparison of LGBT marriages in the perspective of Islamic law and positive Indonesian law.This is a study on normative laws (doctrine) using deductive logic in analyzing primary and secondary legal materials. The results of this study are (1) in the perspective of Islamic laws, same-sex marriage among LGBT is forbidden since it violates the nature and is contrary to maqasid syariah in the sense that it could threaten the essential needs of existence of human beings such as not preserving religion, soul, descendants, mind and honor; (2) in the perspective of positive laws in Indonesia, the state allows merely the marriage between male and female and that it should be in accordance with their religion. Meanwhile, all religions in Indonesia, including Islam, forbid same-sex marriage. Therefore, marriage among LGBT is unlawful and as a result the state does not guarantee their prosperity.